Analysis of cadmium and chromium content in raw and treated leachate from Jerangau-Jabor landfill site, Kuantan, Pahang, Malaysia - How, Fiona Ni Foong; Abang Sapani, Dayang Fatin Nadhirah; Nordin, Nurul Ashikin (2018)
Raw and treated leachate collected from Jerangau-Jabor Landfill Site (JJLS), Kuantan, Pahang, Malaysia were analyzed for the content of cadmium and chromium. The presence of these heavy metals was monitored and analyzed using Flame Atomic Absorption Spectroscopy (FAAS). The metal analyses results were compared with standard value limits from the Environmental Quality (Control of Pollution from Solid Waste Transfer Station and Landfill) Regulations 2009, Malaysian Environmental Quality Act 1974 (Act 127) set by the Department of Environment, Ministry of Natural Resources and Environment, Malaysia. All metal concentrations in the raw leachate were significantly higher than the treated leachate. The concentration of the cadmium in the treated leachate were found to be within the permissible standard limit and showed no potential pollution risk. However, the concentration of chromium in the treated leachate remains high and above the permissible limit stipulated in the regulation as given for chromium hexavalent and chromium trivalent, which was 0.05 mg/L and 0.20 mg/L, respectively. It can be concluded that, a proper treatment for heavy metals such as chromium removal is necessary at JJLS.